Daphne abstract. (1st March 2011) - Hughes, K; Bellis, M A; Calafat, A; Juan, M; Blay, N; Quigg, Z
Abstract : Introduction: Young people's alcohol and drug use increases during holidays. Despite strong associations between substance use and both violence and unintentional injury, little is known about this relationship in young people holidaying abroad. We examine how risks of violence and unintentional injury abroad relate to substance use and the effects of nationality and holiday destination on these relationships. Methods: A cross-sectional comparative survey of 6502 British and German holidaymakers aged 16–35 years was undertaken in airports in Cyprus, Greece, Italy, Portugal and Spain. Results: Overall, 3.8% of participants reported having been in a physical fight (violence) on holiday and 5.9% reported unintentional injury. Two thirds reported having been drunk on holiday and over 10% using illicit drugs. Levels of drunkenness, drug use, violence and unintentional injury all varied with nationality and holiday destination. Violence was independently associated with being male, choosing the destination for its nightlife, staying 8–14 days, smoking and using drugs on holiday, frequent drunkenness, and visiting Majorca (both nationalities) or Crete (British only). Predictors of unintentional injury were being male, younger, using drugs other than just cannabis on holiday, frequent drunkenness and visiting Crete. Conclusions: Violence and unintentional injury are substantial risks for patrons of international resorts offering a hedonistic nightlife. Understanding those characteristics of resorts and their visitors most closely associated with such risks should help inform prevention initiatives which protect both the health of tourists and the economy of resorts marketed as safe and enjoyable places to visit.